The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1007/bf02536122
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of n−3 fatty acids of fish oil into tissue and serum lipids of ruminants

Abstract: This study examines the biohydrogenation and utilization of the C20 and C22 polyenoic fatty acids in ruminants. Eicosapentaenoic (20:5n-3) and docosahexaenoic (22:6n-3) acids were not biohydrogenated to any significant extent by rumen microorganisms, whereas C18 polyenoic fatty acids were extensively hydrogenated. The feeding of protected fish oil increased the proportion of 20:5 from 1% to 13-18% and 22:6 from 2% to 7-9% in serum lipids and there were reductions in the proportion of stearic (18:0) and linolei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
122
7
5

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(151 citation statements)
references
References 12 publications
17
122
7
5
Order By: Relevance
“…The use of the same fish oil previously protected against rumen degradation by coating with formaldehyde-treated casein favours the high incorporation of C20:5n-3 (15 vs. 2% of total FA) and C22:6n-3 (4 vs. 2%) into muscle phospholipids. However, it does not modify the proportion of these fatty acids in triglycerides of intramuscular or external adipose tissues [2]. Similar results have been obtained with fish meal enriched diets.…”
Section: Effects Of Ruminant Feeding On the Nutritional Value Of Meatssupporting
confidence: 83%
“…The use of the same fish oil previously protected against rumen degradation by coating with formaldehyde-treated casein favours the high incorporation of C20:5n-3 (15 vs. 2% of total FA) and C22:6n-3 (4 vs. 2%) into muscle phospholipids. However, it does not modify the proportion of these fatty acids in triglycerides of intramuscular or external adipose tissues [2]. Similar results have been obtained with fish meal enriched diets.…”
Section: Effects Of Ruminant Feeding On the Nutritional Value Of Meatssupporting
confidence: 83%
“…The 22:5 n-3 and 22:6 n-3 levels observed in FO treatment can be attributed to their ruminal BH, despite being supplemented in a protected form. The BH of these PUFAs n-3 can be influenced by the concentration of the FO in the diet (Ashes et al, 1992). Results from a dose-response experiment with FO (Gulati et al, 1999) showed a greater capacity of sheep …”
Section: Resultsmentioning
confidence: 99%
“…Phospholipids are essential constituents of cell membranes and require high levels of PUFAs to maintain membrane properties and physiological functions. Ashes et al (1992) showed that neither 20:5 n-3 and 22:6 n-3 were incorporated into the triacylglycerides of the muscle and adipose tissue, but were transferred into the phospholipids in cattle fed with protected supplements of FO.…”
Section: Milk Fat Depression (Mfd)mentioning
confidence: 99%
“…Factors affecting biohydrogenation of LCPUFA are not well understood, but several studies have indicated that C20:5n-3 and C22:6n-3 are extensively metabolised in the rumen in vivo (Scollan et al, 2001b;Shingfield et al, 2003;Lee et al, 2005). In vitro studies have been less clear with some studies showing limited biohydrogenation (Ashes et al, 1992;Chow et al, 2004), while others showed a decrease (Gulati et al, 1999;Dohme et al, 2003) or an increase in the extent of C20:5n-3 and C22:6n-3 biohydrogenation in relation to FO addition (AbuGhazaleh and Jenkins, (2004).…”
Section: Rumen Functionmentioning
confidence: 99%